IDENTIFIKASI JENIS TELUR NEMATODA YANG TERDAPAT PADA SAYURAN - Suwondo "; Elya Febrita; Lestia Pratiwi (Biogenesis, 2015)
ABSTRACT The aim of reseach was to determine of the eggs of various types of parasitic nematode worms found in vegetables in February and May 2015. The study was conducted with namely the identification of various types of nematode eggs using a survey method. Sampling was done by purposive sampling. The parameters observed in this study are various types of nematode worm eggs rich in vegetable lettuce (Lactuca sativa), basil (Ocimum basilicum L) and cabbage (Brassica oleracea). The results showed that nematode worm eggs found in vegetables lettuce (Lactuca sativa) is Trichuris trichiura and Necator americanus, basil (Ocimum basilicum L) was found on the eggs Ancylostoma duodenale and cabbage (Brassica oleracea) found eggs of Ascaris lumbricoides. Keywords: Nematode worm eggs, Lettuce (Lactuca sativa), Basil (Ocimum basilicum L), Cabbage (Brassica oleracea)